LAMP-LFD Based on Isothermal Amplification of Multicopy Gene ORF160b: Applicability for Highly Sensitive Low-Tech Screening of Allergenic Soybean (Glycine max) in Food. - Allgoewer, Stefanie M.; Hartmann, Chris A.; Lipinski, Clarissa; Mahler, Vera; Randow, Stefanie; Voelker, Elke; Holzhauser, Thomas (Foods, 2020)
Soybean (Glycine max) allergy can be life threatening. A lack of causative immunotherapy of soybean allergy makes soybean avoidance indispensable. Detection methods are essential to verify allergen labeling and unintentional allergen cross contact during food manufacture. Here, we aimed at evaluating our previously described primers for loop-mediated isothermal amplification (LAMP) of multicopy gene ORF160b, combined with a lateral flow dipstick (LFD)-like detection, for their performance of soybean detection in complex food matrices. The results were compared with those obtained using quantitative real-time Polymerase Chain Reaction (qPCR) as the current standard of DNA-based allergen detection, and antibody-based commercial lateral flow device (LFD) as the current reference of protein-based rapid allergen detection. LAMP-LFD allowed unequivocal and reproducible detection of 10 mg/kg soybean incurred in three representative matrices (boiled sausage, chocolate, instant tomato soup), while clear visibility of positive test lines of two commercial LFD tests was between 10 and 102 mg/kg and depending on the matrix. Sensitivity of soybean detection in incurred food matrices, commercial retail samples, as well as various processed soybean products was comparable between LAMP-LFD and qPCR. The DNA-based LAMP-LFD proved to be a simple and low-technology soybean detection tool, showing sensitivity and specificity that is comparable or superior to the investigated commercial protein-based LFD.
EVALuna2:474614
Keywords: multicopy gene; rapid test; loop-mediated isothermal amplification (LAMP); lateral flow dipstick/device (LFD); qPCR; food allergy; allergen detection; soybean; Glycine max